Goma Prateek enriching tamarind wealth - Singh, Sanjay; Singh, A K (Indian Horticulture, 2019)
Tamarind variety, Goma Prateek, was released by Central Institute for Arid Horticulture, Bikaner, during 2009. It outperformed in flowering, fruiting and fruit quality attributes. The tree height and girth are 4.7m and 63.66 cm respectively. It is early, spreading type, regular-bearer, semi-dwarf and starts flowering in fourth year, yielding 58.50 kg fruits/plant.